Telemedicine and Pharmacy: Expanding Access to Medication Therapy Management Services - G. , Prasanthi (International Journal of Psychosocial Rehabilitation, 2020)
The integration of telemedicine into pharmacy practice has ushered in a transformative era for healthcare, particularly in the realm of medication therapy management (MTM) services. This research paper explores the profound impact of telemedicine on expanding access to MTM services, providing an essential platform for the optimal management of medication regimens. Drawing from a comprehensive literature review, this paper illuminates the significance of MTM in healthcare, highlighting the crucial role it plays in patient outcomes and medication adherence. We investigate the evolving landscape of telemedicine and its application in pharmacy, shedding light on the numerous benefits and challenges inherent in this integration. The paper delves into the perspectives of both patients and pharmacists, revealing the tangible advantages telemedicine-based MTM services offer in terms of convenience, accessibility, and improved patient outcomes. It also addresses the economic and regulatory factors influencing the adoption of telemedicine in pharmacy practice. However, this research does not shy away from the ethical, legal, and technological challenges that telemedicine and pharmacy must overcome, along with potential limitations of these services. In conclusion, this research paper underscores the potential of telemedicine to enhance access to MTM services, providing valuable insights into the evolving healthcare landscape and offering guidance for future research, policy, and practice considerations in the telemedicine-pharmacy nexus. As healthcare continues to evolve, telemedicine and pharmacy stand as essential partners in the pursuit of better medication management and improved patient care.